ANALISIS PUBLIC-PRIVATE PARTNERSHIP DALAM PENGEMBANGAN OBJEK WISATA TELAGA SARANGAN DI KABUPATEN MAGETAN - Pratiwi, Nina Galih; Warsono, Hardi (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2018)
The background of this research is the lack of adequate means of transportation to the tourist attraction Sarangan Lake, lack of tourism facilities such as parking space for visitors and lack of quality lodging. The purpose of this research is to explain the function and role of stakeholders that is government, private and society in development of Tourism object of Sarangan Lake in Magetan Regency and also to explain the partnership in development of Tourism object Sarangan Lake.Metode used in this research is descriptive qualitative that is expected to provide a clear picture related to the development of the Sarangan Lake Tourism object. Stakeholders involved in the development of Tourism object Sarangan make coordination through regular meetings yag done periodically then evaluated in mid and end of the year. Partnership between fellow government agencies has reached the degree of action networks or implementation, partnership between the government and the private sector is still lacking. Even this partnership has not yet reached the stage of information networks. Furthermore, partnership between government and society.